PURIFICATION OF WATERS FROM ANIONIC AND CATIONIC SURFACTANTS BY NATURAL ZEOLITES (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
The adsorption of anionic sodium dodecylsulfate (SDS) and cationic cetyltrimethylammonium bromide (CTAB) from aqueous solution on zealots was studied. A series of batch experiments were performed to determine the sorption isotherms of surfactants to zeolite. Furthermore, the isotherm parameters, average percentage errors were calculated. Other factors influencing the adsorption capacity (contact time, adsorbent amount, and initial surfactant concentration) were also discussed. The experimental data fitted very well to the Langmuir and Freundlich equilibrium models. Among the surfactants, CTAB showed higher adsorption capacity onto solid compared with SDS (284 and 113 respectively).
Keywords: adsorption of surfactants, zeolite, Langmuir and Freundlich models, sodium dodecylsulfate, cetyltrimethylammonium bromide